ASSESSMENT OF GENETIC VARIATION AND MODE OF INHERITANCE OF SOME QUANTITATIVE TRAITS IN CHICKPEA (CICER ARIETINUM L.) - N. Hussain; A. Ghaffar; M. Aslam; K. Hussain; Naeem-ud-Din (Journal of Animal and Plant Sciences, 2016)
The present study was conducted to explore the magnitude of genetic variation and mode of inheritance for some quantitative traits among the sixteen genotypes of chickpea at Arid Zone Research Institute, Bhakkar, during the Rabi crop season 2012-13. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. The data regarding eight important quantitative traits was recorded. Four traits viz., number of pods per plant, 100-grain weight, biological yield per plant and grain yield per plant exhibited maximum genetic variation. Genotypic and phenotypic coefficient of variation (GCV and PCV %) was highest for grain yield per plant (19.73 and 20.10) followed by number of pods per plant (18.90 and 19.58), biological yield per plant (13.56 and 14.81) and 100-grain weight (11.60 and 12.25), respectively. High heritability value associated with high genetic advance expressed as percentage of mean was obtained for number of pods per plant (93.19 and 37.59), 100-grain weight (89.67 and 22.62), biological yield per plant (83.83 and 25.58) and grain yield per plant (96.40 and 39.91), respectively. Therefore, these traits can be considered as the most favourable attribute for their improvement due to the contribution of additive gene action and consequently high expected genetic gain from selection.
Keywords: Chickpea; genetic variability; heritability; genetic advance